2016
DOI: 10.1016/j.hpb.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Major liver resection, systemic fibrinolytic activity, and the impact of tranexamic acid

Abstract: Background: Hyperfibrinolysis may occur due to systemic inflammation or hepatic injury that occurs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 48 publications
1
27
0
1
Order By: Relevance
“…A previous open-labelled phase II trial demonstrated that the doses that will be used in our study (loading dose: 1 g; maintenance dose: 1 g/8 hours) provided stable and therapeutic serum concentrations of TXA during major hepatectomy. 25 Furthermore, previous large international RCTs have shown that this dose is safe. 12 13 Despite the potential dose-dependent effect in vitro, higher doses were not adopted because of safety concerns, mainly about seizure.…”
Section: Methods and Analysismentioning
confidence: 96%
“…A previous open-labelled phase II trial demonstrated that the doses that will be used in our study (loading dose: 1 g; maintenance dose: 1 g/8 hours) provided stable and therapeutic serum concentrations of TXA during major hepatectomy. 25 Furthermore, previous large international RCTs have shown that this dose is safe. 12 13 Despite the potential dose-dependent effect in vitro, higher doses were not adopted because of safety concerns, mainly about seizure.…”
Section: Methods and Analysismentioning
confidence: 96%
“…Secondly, we assessed PAI-1 and t-PA plasma concentrations during surgery, before initiation of the Pringle maneuver (T2), in order to evaluate the influence of surgically created tissue damage. Thirdly, we determined the markers at the end of surgery (T3) to assess the impact of liver hypoperfusion on fibrinolytic activity, and fourthly, 24 h after surgery (T4), to detect postoperative fibrinolytic activity, which commonly stays enhanced a few days after liver resection ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…на 5-10 кг массы тела, или 10-15 мл/кг. Свежезамороженная плазма применяется при коагулопатии разведения (и при других состояниях, сопровождающихся дефицитом факторов свертывания) и рекомендуемая доза составляет 1 ед./10 кг, или 10-15 мл/кг [72,73].…”
Section: оригинальные исследованияunclassified